Multi-Channel LED Light Source for Fluorescent Agent Aided Minimally Invasive Surgery - Ren, Jiacheng (Conf Proc IEEE Eng Med Biol Soc, 2014)
Cancer is one of the most common and deadly diseases around the world. Amongst all the different treatments of cancer such as surgery, chemotherapy and radiation therapy, surgical resection is the most effective. Successful surgeries greatly rely on the detection of the accurate tumor size and location, which can be enhanced by contrast agents. Commercial endoscope light sources, however, offer only white light illumination. In this paper, we present the development of a LED endoscope light source that provides 2 light channels plus white light to help surgeons to detect a clear tumor margin during minimally invasive surgeries. By exciting indocyanine green (ICG) and 5-Aminolaevulinic acid (ALA)-induced protoporphyrin IX (PPIX), the light source is intended to give the user a visible image of the tumor margin. This light source is also portable, easy to use and costs less than $300 to build.